Participating in the personal care of a person living with a life-limiting illness in a hospice inpatient setting: the informal caregiver's perspective. (2nd June 2020) - McPherson, Lorraine; Milligan, Stuart; Stevens, Elaine
Abstract : Methods: Using semi-structured interviews, this descriptive qualitative research study examined informal caregivers' perspectives of participating in the personal care of a person living with a life-limiting illness within one hospice inpatient setting. Some 10 principal, informal caregivers of hospice inpatients were recruited by means of purposive sampling, using posters displayed in the hospice inpatient unit. Thus, participation was entirely 'opt-in'. A flash card was displayed at the beginning of each interview to determine a definition of personal care. Field notes and digital audio recording were used to capture data collected. Results: Data were thematically analysed and demonstrated that informal caregivers' perceptions of personal care included everything that allowed the patient to remain the person they were. Informal caregivers reported an acceptable balance between being able to carry out personal care and hospice nursing staff involvement, despite no discussions being carried out to establish their wishes. Prior experiences of informal caregiving, and individual caregiver preparedness, contributed to negative and positive feelings about participating in personal care. Informal caregivers reported additional support and education needs associated with being able to participate in the personal care of patients on discharge and in the future. Conclusions: The emergent themes provide palliative care practitioners with direction for professional practice and research around supporting informal caregivers participating in personal care. Healthcare professionals need to clarify terminology of personal care by having dialogues with informal caregivers and acting on these accordingly. However, not all informal caregivers want such conversations. Consequently, healthcare professionals should approach this topic sensitively. Healthcare professionals ought to be asking informal caregivers if they wish to participate in personal care. Hospice nurses need to engage, support and educate informal caregivers about personal care. Furthermore, they should help to maintain and develop the skills of those informal caregivers who want to continue to play this role and not allow them to become deskilled.